Shifting the Burden: Corporate Indigenous Relations and How They Can Go Wrong - Daniel D. P. McCarthy; Christine A. Daly; Alexandra Davies Post; Gillian Donald; Jean L’Hommecourt; Bori Arrobo; Gregory Hill (Systems)
This paper utilizes the Shifting the Burden Archetype (Senge/Stroh) to document a systemic pattern that is unfortunately, often unconscious to the parties involved and inadvertently leads to the undermining of corporate or government/Indigenous relationships, despite best intentions. Based on over a decade of experience in these contentious contexts, the author(s), document a set of interacting feedback loops that illustrate an unfortunate set of patterns of behaviour, based on starkly different worldviews, in which the choice to engage in more superficial attempts at relationship building actually undermines the ability of the parties to engage in the more difficult but fundamental solution of trust-based relationships. Recommendations for interventions in these typical or archetypal relationships will be made based on an understanding of the dynamics of the system and process design.